PATRÓN DE DISTRIBUCIÓN ESPACIAL Y FLUCTUACIÓN POBLACIONAL DE EUTETRANYCHUS BANKSI (MCGREGOR) (ACARI: TETRANYCHIDAE) Y SU DEPREDADOR EUSEIUS MESEMBRINUS (DEAN) (ACARI: PHYTOSEIIDAE) - Landeros, Jerónimo; Cerna, Ernesto; Badii, Mohammad H.; Varela, Sostenes; Flores, Adriana E. (Instituto de Ecología, A.C., 2004)
With the purpose of determining the type of spatial distribution, populational fluctuation and the possible association spatial and temporal between Texas citrus mite Eutetranychus banksi (McGregor) and his natural predator Euseius mesembrinus (Dean) in Güemez, Tamaulipas 24 samplings were taken during one year, since October 7 ,2000 to September 22, 2001. Eutetranychus banksi presented an aggregated distribution pattern during most of the sampling dates, while E. mesembrinus presented a random distribution pattern. Two population peaks were seen, the first on November 25, 2000 (3.53 and 0.131 ind./ leaf to E. banksi and E. mesembrinus, respectively and the second on April 7, 2001 (12.22 ind./leaf of E. banksi and 0.411 ind./ leaf of E. mesembrinus. We found a significative and positive correlation between E. banksi and E. mesembrinus, (r= 0.982, d.f.= 20 and p= 0.05).